2019
DOI: 10.1111/1467-8268.12390
|View full text |Cite
|
Sign up to set email alerts
|

Banking Sector Development and Energy Consumption in Nigeria: Exploring the Causal Relationship and its Implications

Abstract: This study examines the causal relationship between banking sector development and energy consumption in Nigeria over the period 1971-2013 incorporating crude oil price and indicators of economic performance. An autoregressive distributed lag bounds testing approach to cointegration provides evidence of long-run relationship among the variables. The long-run and short-run estimates suggest that a non-linear inverted U-shaped relationship exists between banking sector development and energy consumption in Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…Many recent studies have relied on the robustness of the statistical properties of ARDL‐bounds model (see Pesaran et al, 2001) to uncover the long‐run relationship among variables (see Abango et al 2019; Aboagye, 2017; Adamu & Rasiah, 2016; Agbanike et al, 2019; Nampewo & Opolot, 2016). In this study, the ARDL‐bounds model is used to check the reliability of the cointegration results in the presence of structural break.…”
Section: Data Empirical Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have relied on the robustness of the statistical properties of ARDL‐bounds model (see Pesaran et al, 2001) to uncover the long‐run relationship among variables (see Abango et al 2019; Aboagye, 2017; Adamu & Rasiah, 2016; Agbanike et al, 2019; Nampewo & Opolot, 2016). In this study, the ARDL‐bounds model is used to check the reliability of the cointegration results in the presence of structural break.…”
Section: Data Empirical Model and Methodologymentioning
confidence: 99%
“…It is expected that the incorporation of financial development into environmental protection policies would create enabling trade and investment environment required to increase investment in cleaner energy technologies. This means that the energy consumption mix could be altered by giving households and firms access to low‐carbon and efficient energy products through policies designed to strengthen the depth of financial intermediation (Agbanike et al, 2019; Anton & Nucu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that banking development significantly affected Middle Eastern countries' levels in the tested economies. According to Agbanike et al (2019), Nigeria's use of nonrenewable energy and banking development are positively correlated. Nguyen (2021) confirmed the beneficial impact of banking growth on Vietnam's level of nonrenewable energy use.…”
Section: Banking Development and Renewable Energy Consumptionmentioning
confidence: 99%
“…1. Aziakpono (2003), King and Levine (1993), Hakeem (2009), Abubakar and Gani (2013), Shahbaz and Lean (2012), Saini and Neog (2018), Gaies et al (2019), Chen et al (2019b), Sadorsky (2011), Aslan et al (2014), Agbanike et al (2019), Gregorio and Guidotti (1995), Olowofeso et al (2015), Prochniak and Wasiak (2017), Sarwar et al (2020), Kapaya (2020), Anetor (2020), Olaniyi and Adedokun (2020), Kwakwa (2021), Haider and Adil (2019), Beck et al (2011), Odeniran and Udeaja (2010), Aziakpono (2003) and Al-mulali and Binti Che Sab (2012).…”
Section: Notementioning
confidence: 99%